(untitled) (ELang | An English Language Education Journal, 2019)
The paper is entitled “Teaching Reading Skills Through Jenga Games” ( Pre-Experimental Study Done in The Second Grade of Junior High School). This research focused on finding out Jenga Games can improve the students’ reading skills. The subject of this research were second grade students of MTs Negeri 1 Bandung. The population of this research is the VIII-A grade of MTs Negeri 1 Bandung, with the 30 students. In conducting this research, the researcher collected the data from the class that was carried out through pre-test, post-test and questionnaire. The result of this result showed that teaching reading skills through jenga games was effective. The result showed that in significance degree of 0.05, the value computation is (7.741 > 2.045 ). It means that t0 (t-observation) is higher than tt (t-table). It could be said that t-test was higher in the than t-table. So, the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. The result showed that the through Jenga Games for teaching reading descriptive text is effective. It means the jenga games technique improve the students reading skills descriptive text in second grade of MTs Negeri 1 Bandung. And the result of questionnaire showed that most students’ agreed that using Jenga Games improve their reading skills, this also means that they gave positive responses. They like, feel fun and easier in using Jenga Games to improve their reading skills. Keywords: Jenga Games, Reading Skills